Isolation and Characterization of vB_kpnM_17-11, a Novel Phage Efficient Against Carbapenem-Resistant Klebsiella pneumoniae - Bai, Jiawei; Zhang, Feiyang; Liang, Shuang; Chen, Qiao; Wang, Wei; Wang, Ying; Martín-Rodríguez, Alberto J.; Sjöling, Åsa; Hu, Renjing; Zhou, Yingshun (Frontiers in Cellular and Infection Microbiology, 2022)
Phages and phage-encoded proteins exhibit promising prospects in the treatment of Carbapenem-Resistant Klebsiella pneumoniae (CRKP) infections. In this study, a novel Klebsiella pneumoniae phage vB_kpnM_17-11 was isolated and identified by using a CRKP host. vB_kpnM_17-11 has an icosahedral head and a retractable tail. The latent and exponential phases were 30 and 60 minutes, respectively; the burst size was 31.7 PFU/cell and the optimal MOI was 0.001. vB_kpnM_17-11 remained stable in a wide range of pH (4-8) and temperature (4-40°C). The genome of vB_kpnM_17-11 is 165,894 bp, double-stranded DNA (dsDNA), containing 275 Open Reading Frames (ORFs). It belongs to the family of Myoviridae, order Caudovirales, and has a close evolutionary relationship with Klebsiella phage PKO111. Sequence analysis showed that the 4530 bp orf022 of vB_kpnM_17-11 encodes a putative depolymerase. In vitro testing demonstrated that vB_kpnM_17-11 can decrease the number of K. pneumoniae by 105-fold. In a mouse model of infection, phage administration improved survival and reduced the number of K. pneumoniae in the abdominal cavity by 104-fold. In conclusion, vB_kpnM_17-11 showed excellent in vitro and in vivo performance against K. pneumoniae infection and constitutes a promising candidate for the development of phage therapy against CRKP.